Do environmental quality, financial inclusion, and good governance ensure the FDI sustainably in Belt and Road countries? Evidence from an application of CS-ARDL and NARDL - JinRu, Long; Qamruzzaman, Md.; Hangyu, Wu; Kler, Rajnish (Frontiers in Environmental Science, 2022)
Domestic capital adequacy and sustainable economic growth immensely rely on technological advancement, managerial know-how, and money supply in the economy. In this context, FDI has emerged and placed at an apex position due to its unprecedented impact on achieving sustainability across the world. The motivation of the study is to scale the effects of good governance, financial inclusion, and environmental quality on inflows of FDI in BRI nations for the period 1990 to 2020. Several panel econometrical tools have been applied, for example, CDS, CADF, CIPS, CS-ARDL, and NARDL, in investigating the association and explanatory variables elasticity on inflows of FDI in BRI nations. CDS results revealed that research units share common dynamism, and second-generation panel unit root test documented variables are stationary after the first difference, and neither has exposed after the first difference. The results of panel cointegration with error correction term have confirmed the long-run association in the empirical equation. According to the CS-ARDL assessment, positive and statistically significant impacts have been documented from financial inclusion, good governance, and environmental quality to FDI inflows. Study findings suggest that governmental effectiveness, easy access to financial services and benefits, and a less regulated environmental concern economy motivate capital transfer decisions. The asymmetric assessment documented a long-run asymmetric association between FI, GG, EQ and FDI. Refers to asymmetric shocks elasticity, the study disclosed a positive and statistically significant tie to FDI inflows, especially in the long run. Directional causality test documented bidirectional casualty running between FI, EQ, GG and FDI [FIFDI; GGFDI; EQFDI] in the short-run.